Strategi Co-Creation Dalam Meningkatkan Daya Saing Umkm Konveksi: Perspektif Pelaku Usaha - Gian Riksa Wibawa; Arif Arif; Haryansyah Aziz; Saskia Nuramelia Sifa; Nafisa Nur Faadhilah (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2026)
This study aims to provide business actors with an understanding of co-creation strategies to enhance competitiveness. Employing a descriptive qualitative methodology, the research focuses on comprehending the phenomenon from the participants' own perspectives. The collected data were analyzed using thematic analysis techniques to identify codes and themes from informant responses. The findings confirm that the implementation of a co-creation approach positively influences the strengthening of MSME competitiveness. Involving customers in the product design and development process fosters a sense of acknowledgment, which in turn enhances customer loyalty. Conversely, the study identifies several challenges, including limited production capacity, constraints in raw material availability, production timelines, and difficulties in realizing design concepts. For the optimal implementation of this strategy, government support is essential. It is recommended that the government provide training and other forms of assistance to MSMEs to foster more innovative co-creation practices, enabling them to leverage it as a strategic opportunity in the market competition. Practically, these findings encourage MSME actors to adopt co-creation more systematically, particularly by optimizing digital media and managing customer interactions effectively.